Revisiting the Lexical Differences Between Academic and General Training IELTS Reading Tests - Linh Thi Thao Le; Nam Thi Phuong Ho; Nguyen Huynh Trang; Hung Tan Ha (SAGE Open)
The International English Language Testing System (IELTS) has served as one of the most reliable proofs of people’s English language proficiency. There have been rumors about the discrepancy in difficulty between the two modules of IELTS, namely Academic (AC) and General Training (GT); however, there is little empirical evidence to confirm such a myth. This research directly compares the lexical demands, diversity, and sophistication between the reading passages in three sections of the two IELTS Reading test modules. 345 IELTS reading passages from 115 IELTS Reading tests were analyzed in terms of length, lexical diversity, sophistication, and demands. Results from the pairwise comparisons show significant differences between the three reading passages of the AC module and the first two reading sections of the GT module in terms of length and lexical sophistication. However, research findings also demonstrate insignificant differences between the AC passages and the last GT passage. In addition, results from lexical demand analyses confirm these findings by indicating that, for the AC reading passages and the last GT passage, learners need to be familiar with the most frequent 4,000 and 9,000 word families in the BNC/COCA lists to achieve 95% and 98% coverage, respectively. On the other hand, the first and second sections in the GT module only require a vocabulary knowledge at 3,000 to 6,000 levels for 95% and 98% coverage, correspondingly. Ultimately, implications for IELTS teaching and learning will be discussed.